E=6c^2−2c−1 F=−4c^2+7c+5 ​ E+F=

Question

E=6c^2−2c−1

F=−4c^2+7c+5

E+F=

in progress 0
Quinn 1 week 2021-11-20T14:53:54+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-20T14:55:14+00:00

    The answer of given equation is 2c^{2} + 5c +4

    Step-by-step explanation:

    By putting the given values of E and F we get,

    E + F

    =( 6c^{2}-2c-1) + (-4c^{2}+7c+5)

    Here we will take the coefficient of same variable together

    =(6c^{2}-4c^{2}) +( -2c +7c) +( -1+5)

    =2c^{2} + 5c +4

    Hope this helps you.

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )